Statutory Speedy Trial Period Calculations for Dismissed and Refiled Charges: A Case Study of Colorado’s Approach - Marie Zoglo (Washington University Law Review, 2020)
Colorado’s current approach of allowing the speedy trial period to restart creates too large a loophole in the state’s statutory right to a speedy trial within six months because it grants too much leeway to prosecutors. As courts have yet to apply the exception to restarting upon a showing that the prosecution dismissed and refiled to circumvent the speedy mandate, the exception is too vague to provide sufficient notice to courts, prosecutors, and defendants about when the exception applies, if it ever does. Moreover, because the restarting approach forces courts to make fact-specific inquiries into the prosecution’s motives for dismissal and refiling and because it overincentivizes dismissals and refilings, the approach creates inefficiencies in the justice system. It also permits prosecutors to infringe on the powers of the courts by essentially allowing prosecutors to grant themselves unauthorized continuances. Colorado should adopt the tacking-and-tolling approach. This approach best balances the countervailing interests of society and defendants in speedy trials, while still rarely allowing the guilty to escape justice on technical speedy trial violations instead of the merits of their cases. Additionally, the tacking-and-tolling approach is most consistent with Colorado’s constitutional speedy trial rights. Lastly, this approach best incentivizes efficiency in the justice system.
Keywords: Speedy trial period; Right to a speedy trial; Prosecutorial discretion; Tacking-and-tolling; Criminal charges